A decision analytic model to investigate the cost-effectiveness of poisoning prevention practices in households with young children - Achana, F; Sutton, AJ; Kendrick, D; Hayes, M; Jones, DR; Hubbard, SJ; Cooper, NJ (BioMed Central, 2016)
Background Systematic reviews and a network meta-analysis show home safety education with or without the provision of safety equipment is effective in promoting poison prevention behaviours in households with children. This paper compares the cost-effectiveness of home safety interventions to promote poison prevention practices.